Infections in patients with mantle cell lymphoma - Kossi D. Abalo; Sara Ekberg; Therese M. L. Andersson; Simon Pahnke; Alexandra Albertsson‐Lindblad; Karin E. Smedby; Mats Jerkeman; Ingrid Glimelius (HemaSphere, 2024)
Abstract Advancements in treatments have significantly improved the prognosis for mantle cell lymphoma (MCL), and there is a growing population of survivors with an increased susceptibility to infections. We assessed the incidence of infections by clinical characteristics and treatment both before and after MCL diagnosis in Sweden. Patients with a diagnosis of MCL ≥ 18 years between 2007 and 2019 were included, along with up to 10 matched comparators. Infectious disease diagnosis and anti‐infective drug dispensation were identified by the National Patient and the Prescribed Drug Registers, respectively. Patients and comparators were followed from the diagnosis/matching date until death, emigration, or June 30, 2020. Overall, 1559 patients and 15,571 comparators were followed for a median duration of 2.9 and 5 years, respectively. The infection rate among patients was twofold higher, RRadj = 2.14 (2.01–2.27), contrasted to the comparator group. There was a notable rise in infection rates already 4 years before MCL diagnosis, which reached a fourfold increase in the first year after diagnosis and persisted significantly increased for an additional 8 years. Among patients, 69% (n = 1080) experienced at least one infection during the first year of follow‐up. Influenza, pneumonia, other bacterial infections, urinary tract infections, and acute upper respiratory infections were the most frequent. Notably, MCL remained to be the primary leading cause of death among patients (57%, n = 467/817). Infections as the main cause of death were rare (2.6%, n = 21). Our study highlights the importance of thoroughly assessing infectious morbidity when appraising new treatments. Further investigations are warranted to explore strategies for reducing infectious disease burden.